Hubungan Konsep Diri, Sikap Guru Terhadap Pekerjaan dan Pengalaman Menjadi Guru dengan Kemampuan Mengajar Guru di Smp Negeri di Kota Palangka Raya - Sonedi Sonedi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
These results showed that : (1) there is a significant correlation between self-concept and the ability of teachers to teach in the State Junior High School in Palangka Raya, amounting to 35.9%; (2) the results of research on teacher attitudes towards work gives a significant correlation with the teachers' teaching ability. Teacher attitudes toward work are able to contribute to the teaching capabilities of teachers by 41.2%; (3) the experience of being a teacher giving a significant correlation to the ability of teachers to teach. The experience of being a teacher is able to explain the ability of teachers to teach at 39.3%. (4) there is a significant correlation between self-concept, attitude towards the work of teachers, and the teachers' teaching experience in State Junior High School in Palangkaraya. These three independent variables jointly contribute significantly to the ability of teachers to teach, especially in this study amounted to 58.3%. (5) There is a correlation between the variables self-concept, attitudes of teachers towards work and experience as a teacher with the ability of teachers to teach. Variable attitude of teachers towards work (41.2%), is the most dominant variable related to the ability of teachers to teach.